Collaboration and resistance Catalino Hermosilla and the Japanese occupation of Ormoc, Leyte (1942-1945) - Ara, Satoshi (Philippine studies : historical and ethnographic viewpoints, 2012)
"This article presents local history in Leyte, Philippines, during the Japanese occupation, examining in particular the nature of collaborationism by Ormoc Mayor Catalino Hermosilla. In the context of local political feuds, this study shows how Hermosilla's collaboration with the Japanese enabled him not so much to advance Japanese goals but to strengthen his political power base. However, contrary to the view that the Japanese occupation did not alter social dynamics, this stud shows that, although Ormoc's oligarchy remained conspicuous after the war, an important change had occurred as seen in the waning of Hermosilla's clout in municipal politics.